Generation and characterization of human iPSC line SANi012-A from a patient with an inherited platelet disorder carrying the heterozygous ETV6 c.1105C > T variant - Huan Zhang; Chantal C. Clark; Elise J. Huisman; Marieke von Lindern; Marjon H. Cnossen; Emile van den Akker; Eszter Varga (Stem Cell Research, 2025)
Germline mutations in ETV6, a transcription factor of the ETS family, are associated with autosomal dominant thrombocytopenia and an increased risk of leukemia. We generated a human iPSC line, SANi012-A, from a patient carrying a heterozygous ETV6 c.1105C > T missense mutation. Proerythroblasts from the patient’s peripheral blood mononuclear cells (PBMCs) were reprogrammed using a lentiviral hOKSM polycistronic vector. The iPSC line showed normal karyotype and morphology, expressed pluripotency markers, and were able to differentiate into all three germ layers.